GEOPARK KALDERA TOBA DIMANFAATKAN SEBAGAI INSTRUMEN SOFT POWER DIPLOMACY OLEH INDONESIA DALAM MEMPROMOSIKAN CITRA POSITIF NEGARA DI TINGKAT INTERNASIONAL - Ribka Sijabat; Ibnu Zulian (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
The Toba Caldera Geopark is a global geological heritage area with strategic scientific, ecological, and cultural value for Indonesia in the context of contemporary international relations. This study analyzes how the Toba Caldera Geopark is utilized as an instrument of soft power diplomacy to strengthen Indonesia's image internationally. Using Joseph Nye's soft power theoretical framework, nation branding, and cultural, environmental, and scientific diplomacy, this study explores the development of geopark narratives as a non-coercive diplomatic tool. The methodology used is a descriptive qualitative analysis with an interpretative approach based on literature data, government policies, UNESCO reports, and official tourism promotion narratives. The results show that the Toba Caldera Geopark plays a multidimensional role in Indonesian diplomacy, including the promotion of sustainable tourism, participation in the UNESCO Global Geopark Network, international research collaboration, cultural diplomacy through Batak festivals and art performances, and environmental diplomacy that emphasizes Indonesia's commitment to conservation and green development. However, challenges in environmental governance, pollution, the pressure of mass tourism, and the imbalance in human resource capacity still have the potential to weaken the effectiveness of geoparks as a diplomatic instrument. This study concludes that the Toba Caldera Geopark has become an important symbol of Indonesia's soft power, but its sustainability depends on strengthening collaborative governance, digital diplomacy innovation, and synergy between actors across sectors.